ANALYSIS OF CONCRETE COMPRESSIVE STRENGTH WITH PARTIAL SUBSTITUTION OF IRON POWDER WASTE AS FINE AGGREGATE - DELLA GIOVANNI; YONAS PRIMA ARGA RUMBYARSO; BERMANDO SIAGIAN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
This study evaluates the use of iron powder waste as a partial replacement of fine aggregate in concrete to reduce environmental impacts. By testing various percentages of iron powder (0%, 7.5%, and 12.5%), this study analyzed the compressive strength of concrete at the ages of 7, 14, and 28 days. The results showed that the addition of iron powder tended to reduce the compressive strength of concrete compared to normal concrete. Concrete with 7.5% iron powder had better compressive strength compared to 12.5%, but both had not reached the expected compressive strength. Further research is needed to find the optimal combination of iron powder and other additional materials.